2000
DOI: 10.1103/physrevlett.84.3911
|View full text |Cite
|
Sign up to set email alerts
|

Critical Fluctuations and Quenched Disordered Two-Dimensional Charge Stripes inLa5/3Sr1/3NiO

Abstract: Using high-resolution x-ray scattering, we have demonstrated the existence of quenched disordered charge stripes in a single crystal of La (5/3)Sr (1/3)NiO (4) at low temperatures. Above the second-order transition critical scattering was observed due to fluctuations into the charge stripe phase. The charge stripes are shown to be two dimensional in nature both by measurements of their correlation lengths (xi(a) approximately 185 A, xi(b) = 400 A, and xi(c) approximately 25 A) and by the critical exponents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
52
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 19 publications
12
52
2
Order By: Relevance
“…Under the assumption that all of the measurements are probing the same CDW correlations, it has been proposed that the X-ray measurements might be integrating over fluctuating CDW correlations, which would not be detectable by NMR 48,49 . There are problems with such an interpretation, however, a recent study 50 has shown that the integrated intensity of a CDW peak in YBa 2 Cu 3 O 6.6 is quite similar to one in charge-stripe-ordered La 1 NiO 4 , our results directly demonstrate that charge-stripe fluctuations exist far above T co , whereas elastic X-ray scattering measurements 16 lost the signal by T co þ 20 K. This strongly suggests that the X-ray studies of YBa 2 Cu 3 O 6 þ x are measuring static correlations. (Note that recent inelastic X-ray scattering measurements 51 have narrowed the possible energy range of fluctuations to something less than 1 meV.)…”
Section: Discussioncontrasting
confidence: 38%
“…Under the assumption that all of the measurements are probing the same CDW correlations, it has been proposed that the X-ray measurements might be integrating over fluctuating CDW correlations, which would not be detectable by NMR 48,49 . There are problems with such an interpretation, however, a recent study 50 has shown that the integrated intensity of a CDW peak in YBa 2 Cu 3 O 6.6 is quite similar to one in charge-stripe-ordered La 1 NiO 4 , our results directly demonstrate that charge-stripe fluctuations exist far above T co , whereas elastic X-ray scattering measurements 16 lost the signal by T co þ 20 K. This strongly suggests that the X-ray studies of YBa 2 Cu 3 O 6 þ x are measuring static correlations. (Note that recent inelastic X-ray scattering measurements 51 have narrowed the possible energy range of fluctuations to something less than 1 meV.)…”
Section: Discussioncontrasting
confidence: 38%
“…This evidences that charge stripes undergo a second-order phase transition. This is consistent with our previous report of a quenched disordered charge stripes [22]. According to our model, this quenched disordered state is the consequence of the interplay between charges and spins.…”
Section: (E)supporting
confidence: 82%
“…Finally, the interlayer charge correlation length reaches ξ = ∼10Å below T = 218 K, where both the charge and spin stripes are well established. We realize, for the c-axis correlation length at low temperatures, that there exists a discrepancy between the current data and the reported result [22]. This difference could be due to the different sample treatments as those reported by Hücker et al [21].…”
Section: (E)contrasting
confidence: 54%
See 2 more Smart Citations